Henoch-Schönlein purpura and drug and vaccine use in childhood: a case-control study. Issue 1 (December 2016) - Da Dalt, Liviana; Zerbinati, Claudia; Strafella, Maria; Renna, Salvatore; Riceputi, Laura; Di Pietro, Pasquale; Barabino, Paola; Scanferla, Stefania; Raucci, Umberto; Mores, Nadia; Compagnone, Adele; Da Cas, Roberto; et al.
Abstract Background Henoch-Schönlein purpura (HSP) is the most common vasculitis in childhood; nevertheless, its etiology and pathogenesis remain unknown despite the fact that a variety of factors, mainly infectious agents, drugs and vaccines have been suggested as triggers for the disease. The aim of this study was to estimate the association of HSP with drug and vaccine administration in a pediatric population. Methods An active surveillance on drug and vaccine safety in children is ongoing in 11 clinical centers in Italy. All children hospitalized through the local Paediatric Emergency Department for selected acute clinical conditions of interest were enrolled in the study. Data on drug and vaccine use in children before the onset of symptoms leading to hospitalization were collected by parents interview. A case-control design was applied for risk estimates: exposure in children with HSP, included as cases, was compared with similar exposure in children with gastroduodenal lesions, enrolled as controls. HSP cases were validated according to EULAR/PRINTO/PRES criteria. Validation was conducted retrieving data from individual patient clinical record. Results During the study period (November 1999–April 2013), 288 cases and 617 controls were included. No increased risk of HSP was estimated for any drug. Among vaccines, measles-mumps-rubella (MMR) vaccine showed an increased risk of HSP (OR 3.4; 95 % CI 1.2–10.0). Conclusions This study provides further evidence on the possible role of MMR vaccine in HSP occurrence.